Genesis of the South Asian High and Its Impact on the Asian Summer Monsoon Onset - Liu, Boqi; Wu, Guoxiong; Mao, Jiangyu; He, Jinhai (Journal of climate, 2013)
The formation of the South Asian high (SAH) in spring and its impacts on the Asian summer monsoon onset are studied using daily 40-yr ECMWF Re-Analysis (ERA-40) data together with a climate-mean composite technique and potential vorticity–diabatic heating (PV–Q) analysis. Results demonstrate that, about 2 weeks before the Asian summer monsoon onset, a burst of convection over the southern Philippines produces a negative vorticity source to its north. The SAH in the upper troposphere over the South China Sea is then generated as an atmospheric response to this negative vorticity forcing with the streamline field manifesting a Gill-type pattern. Afterward, the persistent rainfall over the northern Indochinese peninsula causes the SAH to move westward toward the peninsula. Consequently, a trumpet-shaped flow field is formed to its southwest, resulting in divergence pumping and atmospheric ascent just over the southeastern Bay of Bengal (BOB). Near the surface, as a surface anticyclone is formed over the northern BOB, an SST warm pool is generated in the central–eastern BOB. This, together with SAH pumping, triggers the formation of a monsoon onset vortex (MOV) with strong surface southwesterly developed over the BOB. Enhanced air–sea interaction promotes the further development and northward migration of the MOV. Consequently, the wintertime zonal-orientated subtropical anticyclone belt in the lower troposphere splits, abundant water vapor is transported directly from the BOB to the subtropical continent, and heavy rainfall ensues; the atmospheric circulation changes from winter to summer conditions over the BOB and Asian summer monsoon onset occurs.